Programa de certificación ambiental para agricultores de Colombia (2024)
"The analysis of the international and national situation on the management of agrochemicals highlights the importance of promoting sustainable agricultural practices. Examples are seen from Spain and the European Union that have implemented regulations and training programs to ensure responsible use of agrochemicals. In Colombia, Good Agricultural Practices (GAP) certification has been implemented to encourage responsible and sustainable practices. The results of the research reveal that, although there is recognition of the importance of training, there are logistical and economic barriers that limit the participation of farmers. However, there is a clear interest in participating if financial incentives are offered. An Environmental Certification Program for Farmers in Colombia is proposed that includes face-to-face training in the villages, economic incentives and GAP certification. This strategy seeks to improve agricultural practices, protect the environment and ensure a more sustainable and economically viable agriculture."